Pengembangan Mobile Learning Disertai Constructive Feedback pada Materi Induksi Elektromagnetik untuk Siswa SMA/MA - Handayani, Indah Dwi; Sulur, Sulur; Pramono, Nugroho Adi; Nurani, Budi; Wigiyati, Catur (Jurnal Riset Pendidikan Fisika, 2021)
Mobile learning has been developed with constructive feedback to determine the feasibility level of mobile learning with constructive feedback on Electromagnetic Induction material for SMA/MA students at the limited trial stage. This development uses a 4D model, but until stage 3 (develop) it does not reach stage 4 (disseminate). The product that has been developed is then validated by three validators (one physics lecturer at FMIPA UM and two physics teachers at SMAN 3 Malang) including content validation, construct validation, claim validation, and constructive feedback validation and tested for practicality on 28 students of class XII MIPA C-6 SMAN 3 Malang. Quantitative data and qualitative data are types of data in this research and development. Quantitative data was obtained from the results of the assessment using a Likert Scale for a validation questionnaire and a Guttman Scale for a practicality questionnaire. The analysis technique for quantitative data was calculated using the average calculation. The analytical technique used in the practicality test uses percentage calculations. Based on the results of data analysis, it is found that the mobile learning application with constructive feedback is a feasible application with a validity level of 3.78 and a practicality test of 93.58%. Based on the results of the validation and limited trials, it can be concluded that the mobile learning application accompanied by constructive feedback on Electromagnetic Induction material is suitable for students to use for independent study, so as to improve understanding of concepts and motivation in learning activities.Keywords:   Mobile learning, constructive feedback, electromagnetic induction ABSTRAKTelah dikembangkan mobile learning disertai constructive feedback untuk mengetahui tingkat kelayakan mobile learning disertai constructive feedback pada materi Induksi Elektromagnetik untuk siswa SMA/MA pada tahap uji coba terbatas. Pengembangan ini menggunakan model 4D, tetapi sampai tahap 3 (develop) tidak sampai tahap 4 (disseminate). Produk yang telah dikembangkan kemudian divalidasi oleh tiga validator (satu dosen Fisika FMIPA UM dan dua guru fisika di SMAN 3 Malang) meliputi validasi konten, validasi konstruk, validasi klaim, serta validasi constructive feedback dan diuji kepraktisan pada 28 siswa kelas XII MIPA C-6 SMAN 3 Malang. Data kuantitatif dan data kualitatif merupakan jenis data dalam penelitian dan pengembangan ini.  Data kuantitatif diperoleh dari hasil penilaian menggunakan Skala Likert untuk angket validasi dan Skala Guttman untuk angket kepraktisan. Teknik analisis untuk data kuantitatif dihitung menggunakan perhitungan rata-rata. Teknik analisis yang digunakan pada uji kepraktisan menggunakan perhitungan persentase.Berdasarkan hasil analisis data diperoleh bahwa aplikasi mobile learning disertai constructive feedback adalah aplikasi yang layak dengan tingkat kevalidan 3,78 dan uji kepraktisan sebesar 93,58%. Berdasarkan hasil validasi dan uji coba terbatas maka dapat disimpulkan bahwa aplikasi mobile learning disertai constructive feedback pada materi Induksi Elektromagnetik layak digunakan oleh siswa untuk belajar mandiri, sehingga dapat meningkatkan pemahaman konsep dan motivasi dalam kegiatan belajar.Kata Kunci:  Mobile learning, constructive feedback, induksi elektromagnetik